2020
DOI: 10.1101/2020.09.07.285502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated detection of Hainan gibbon calls for passive acoustic monitoring

Abstract: 1AbstractExtracting species calls from passive acoustic recordings is a common preliminary step to ecological analysis. For many species, particularly those occupying noisy, acoustically variable habitats, the call extraction process continues to be largely manual, a time-consuming and increasingly unsustainable process. Deep neural networks have been shown to offer excellent performance across a range of acoustic classification applications, but are relatively underused in ecology.We describe the steps involv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…Artificial neural networks gained popularity in many fields of biology during the last decade [60]. For example, they have been used for behavioural classification from tri-axial acceleration data [6163] or from GPS data [64,65] and to model datasets with high temporal resolution [63,64,66].…”
Section: Methodsmentioning
confidence: 99%
“…Artificial neural networks gained popularity in many fields of biology during the last decade [60]. For example, they have been used for behavioural classification from tri-axial acceleration data [6163] or from GPS data [64,65] and to model datasets with high temporal resolution [63,64,66].…”
Section: Methodsmentioning
confidence: 99%
“…While the human speech separation problem is a competitive area of work, the bioacoustic CPP has received comparatively less attention, as current bioacoustic research often emphasizes other ML-based tasks such as automated detection and classification of bioacoustic sounds [30][31][32] . However, recent work has implemented both semi-classical and deep ML-based approaches to address bioacoustic source separation, employing time domain and TFR-based algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…While for clean, loud calls accurate species-level recognition has been possible for several years now, the performance dramatically drops when moving to noisy and sparse recordings (Goëau et al, 2016), and has remained a challenge since (Kahl et al, 2020). Some recently explored approaches to overcome this are: testing different network architectures and meta-structures (Ibrahim et al, 2021;Dufourq et al, 2021;Merchan et al, 2020), adding separate networks for noise learning and removal , optimising spectrogram pre-processing for CNNs (Knight et al, 2019;Merchan et al, 2020), learning more robust features directly from the waveform (Sanchez et al, 2021). These studies have reported good performance on their respective target species.…”
Section: Machine Learning Literaturementioning
confidence: 99%
“…However, achieving good results with CNNs so far has required thousands of labelled examples for each species; see e.g. Zhong et al (2020); Dufourq et al (2021). Collecting such datasets is difficult and expensive in bioacoustics.…”
Section: Machine Learning Literaturementioning
confidence: 99%
See 1 more Smart Citation